Efficiency of local injections of platelet-rich plasma in shoulder impingement syndrome - V. A. Nesterenko; A. E. Karateev; E. I. Byalik; M. A. Makarov; S. A. Makarov; V. E. Byalik; M. R. Nurmukhametov; I. A. Fedotov (Современная ревматология, 2019)
Chronic shoulder pain caused by shoulder impingement syndrome (SIS) is a common pathology that leads to worse quality of life and disability. The local administration of platelet-rich plasma (PRP) is a promising treatment for SIS.Objective: to evaluate the efficiency of subacromial injection of PRP in chronic shoulder pain caused by SIS.Patients and methods. The investigation enrolled 30 patients (13 women and 17 men; mean age, 45.8±14.1 years) with chronic shoulder pain lasting ≥3 months after rotator tendons injury confirmed by ultrasound and/or magnetic resonance imaging and inefficiency of previously medical therapy. All the patients received three subacromial injections of 5 ml of PRP at a 7-day interval. The investigators assessed the course of pain during movement (100-mm visual analogue scale (VAS)) and functional ability according to the ASES and CSC questionnaires at baseline and 1, 3 and 6 months after treatment.Results and discussion. During the treatment, there was a considerable improvement in all indicators. At baseline and 1 and 3 months, the mean pain severity measured on VAS was 49.3±10.3, 32.4±21.3, and 20.6±21.3 mm, respectively; in this case, the positive effect persisted at 6-month follow-up: 10 [0; 30] mm (p<0.001). The mean ASES values were 59.5±11.5, 75.9±17.4, 82.6±17.6, and 86.7±17.1 (p<0.001) and the mean CSC scores were 72.3±14.1, 81.0±16.2, 88.5±16.1, and 92.8±16.2 (p<0.001), respectively. There were no serious adverse reactions.Conclusion. Subacromial injection of PRP is an effective and safe treatment for chronic shoulder pain associated with SIS.